Impact of Technology on Risk Management in Banks - Shroff, Firdos T. (SFIMAR Research Review, 2016)
Introduction of the topic: The topic covers the technology risk and managing it in banks. There are various types of risks and one of them is operational and technology risks. Risk cannot be avoided but it could be mitigated. The financial crisis exposed inherent weaknesses in the risk management system: soloed infrastructures, disparate systems and processes, fragmented decision-making, inadequate forecasting and a dearth of cohesive reporting, among others. The impact of these flaws on many institutions shocked the industry. As a result, there has been a seismic shift in attitude toward risk. Three ways banks are rethinking risk strategies: Many executives believe that the industry's heightened focus on risk governance is one of the Most positive outcomes of the crisis, forcing senior management to fundamentally rethink their strategic approach to risk, below are three approaches global banks are taking. 1) Reassessing and integrating risk appetite: boards and senior management are clearly defining risk tolerance and limits. 2) Strengthening risk identification processes: banks are looking at risk holistically and assuming a more vigilant stance on risk identification policies and procedures. 3) Shifting focus on riskclasses: new areas of riskare surfacing on senior management agendas.